Rho Kinase Inhibition by AT13148 Blocks Pancreatic Ductal Adenocarcinoma Invasion and Tumor Growth - Rath, Nicola; Munro, June; Cutiongco, Marie Francene; Jagiełło, Alicja; Gadegaard, Nikolaj; McGarry, Lynn; Unbekandt, Mathieu; Michalopoulou, Evdokia; Kamphorst, Jurre J; Sumpton, David; Mackay, Gillian; Vennin, Claire; et al. (Cancer research (Chicago, Ill.), 2018)
The high mortality of pancreatic cancer demands that new therapeutic avenues be developed. The orally available small-molecule inhibitor AT13148 potently inhibits ROCK1 and ROCK2 kinases that regulate the actomyosin cytoskeleton. We previously reported that ROCK kinase expression increases with human and mouse pancreatic cancer progression and that conditional ROCK activation accelerates mortality in a genetically modified ; (KPC) mouse pancreatic cancer model. In this study, we show that treatment of KPC mouse and human TKCC5 patient-derived pancreatic tumor cells with AT13148, as well as the ROCK-selective inhibitors Y27632 and H1152, act comparably in blocking ROCK substrate phosphorylation. AT13148, Y27632, and H1152 induced morphologic changes and reduced cellular contractile force generation, motility on pliable discontinuous substrates, and three-dimensional collagen matrix invasion. AT13148 treatment reduced subcutaneous tumor growth and blocked invasion of healthy pancreatic tissue by KPC tumor cells without affecting proliferation, suggesting a role for local tissue invasion as a contributor to primary tumor growth. These results suggest that AT13148 has antitumor properties that may be beneficial in combination therapies or in the adjuvant setting to reduce pancreatic cancer cell invasion and slow primary tumor growth. AT13148 might also have the additional benefit of enabling tumor resection by maintaining separation between tumor and healthy tissue boundaries. Preclinical evaluation of a small-molecule ROCK inhibitor reveals significant effects on PDAC invasion and tumor growth, further validating ROCK kinases as viable therapeutic targets in pancreatic cancer. .